Outside the Networks. Aurora Olin’s and Saima Grönstrand’s struggles as female editors in the turn-of-the-20th-century Finnish press. - Sorvali, Satu; Hänninen, Reetta (Journalistica, 2026)
In this article, we examine Aurora Olin (1855–1924) and Saima Grönstrand (1863–1932) through the lenses of journal editing, journalistic networks, and their biographies. They were among the first women journalists in the Finnish press, and their women’s journals were some of the earliest produced outside the suffragette movement by a private person. Not only did they not establish their own journals, Kodin-Ystävä (Home’s friend) and Kalevatar (Woman of Kalevala), but also took sole responsibility for the editorial work and, to a very large extent, the production of content for the journals. These women serve as excellent examples of how challenging it was to establish and publish periodicals at the turn of the 19th and 20th centuries, especially for women who had sole responsibility for finances, editing, and content creation. Both women had the education and the opportunities – nevertheless, the lack of wealth and networks made it hard to succeed.